Risk of disease as a criterion of medical-environmental conditions of the quality of life - V. M. Prusakov; A. V. Prusakova (Acta Biomedica Scientifica, 2013)
Evaluation of features forming a local variant of population health, depending on local conditions is one of the urgent tasks for the study of preventive measures to improve the level of health and quality of life in specific areas. The aim of the work was the formation of local type of population health and environmental health components of quality of life in the industrialized areas of the Irkutsk region with use of indicators of the risk of disease. To solve this purpose the data of the prevalence of certain diseases and all classes of primary uptake of children and teenagers in the industrial cities of Irkutsk region with high levels of air pollution was used. Changes in environmental load assessed by the dynamics of total emissions of harmful substances and by terms of air pollution. Prevalence of environmentally caused diseases of children and teenagers in the research area and the degree of intensity of medical and environmental situation of the different areas with the definition of the category of its distress was assessed in terms of the relative risks of morbidity diseases of individual classes and all classes in the dynamics of the data and five-year periods. The local type of health of the industrial city in terms of ecological-depended morbidity was ranked by the number of classes of diseases and they determine the category of tension health and environmental situation. The possible impact of air pollution on the health of the population was analyzed with the possible evolution of the state of nonspecific increased resistance of children and teenagersfrom exposure to pollutants and other environmental factors. The presented results of the evaluation of the dynamics of health and environmental situation in the industrialized cities of Irkutsk region suggest that the relative risks of morbidity allows to define a local version of population health and to assess the environmental health component of quality of life in industrialized areas.